Profile of esophageal squamous cell carcinoma mutations in Brazilian patients - Fernanda Franco Munari; Wellington dos Santos; Adriane Feijó Evangelista; Ana Carolina Carvalho; Paula Aguiar Pastrez; Diego Bugatti; Durval R. Wohnrath; Cristovam Scapulatempo-Neto; Denise Peixoto Guimarães; Adhemar Longatto-Filho; Rui Manuel Reis (Scientific Reports, 2021)
Abstract Esophageal cancer is an aggressive tumor that has a high rate of incidence and mortality worldwide. It is the 10th most frequent type in Brazil, being squamous cell carcinoma (ESCC) the predominant subtype. There is currently an incessant search to identify the frequently altered genes associated with esophageal squamous cell carcinoma biology that could be druggable. This study aimed to analyze the somatic mutation profile of a large panel of cancer-related genes in Brazilian ESCC. In a series of 46 ESCC diagnoses at Barretos Cancer Hospital, DNA isolated from paired fresh-frozen and blood tissue, a panel of 150 cancer-related genes was analyzed by next-generation sequencing. The genes with the highest frequency of mutations were TP53 (39/46, 84.8%), followed by NOTCH1 (7/46, 15.2%), NFE2L2 (5/46, 10.8%), RB1 (3/46, 6.5%), PTEN (3/46, 6.5%), CDKN2A (3/46, 6.5%), PTCH1 (2/46, 4.3%) and PIK3CA (2/46, 4.3%). There was no significant association between molecular and patients’ clinicopathological features. Applying an evolutionary action score of p53 (EAp53), we observed that 14 (35.9%) TP53 mutations were classified as high-risk, yet no association with overall survival was observed. Concluding, this the largest mutation profile of Brazilian ESCC patients, which helps in the elucidation of the major cancer-related genes in this population.